Determination of current transport and trap states density in AlInGaN/GaN heterostructures. (December 2019) - Arslan, Engin; Ural, Sertaç; Altındal, Şemsettin; Özbay, Ekmel
Abstract: The energy distribution and the relaxation time constant of the trap states with respect to conduction bands in the (Ni/Au) Schottky contact on AlInGaN/GaN heterostructures were investigated using the admittance technique. The potential dependent capacitance/conductance measurements were done in the frequency range of 5 kHz to 5 MHz at a temperature of 300 K. We found strong frequency dispersions at the accumulation regions and at the sharp transition regions (depletion region) in the capacitance curves. High frequency dispersion at the accumulation regions in C - V characteristics indicates that there is a high-density of surface traps between the metal–AlInGaN quaternary layer interfaces. Furthermore, the frequency dispersion at the sharp transition regions behavior can be attributed to the interface traps state between the AlInGaN quaternary layer and GaN layer. A detailed analysis of the frequency-dependent capacitance and conductance data was performed, assuming the models in which traps are located between the metal–AlInGaN interface (surface traps) and between AlInGaN/GaN interfaces (interface traps). The trap states density and time constants of the traps states were calculated as a function of energy separation from the conduction-band edge. The trap states' densities change between 1.3 × 10 11  eV −1  cm −2 and 6.2 × 10 11  eV −1  cm −2 . Also, 4.8 to 5.3 μs time interval calculated for the relaxation times. Highlights: Current-transport behavior, energy distribution and relaxation time constant calculations of trap states in AlInGaN/GaN heterostructures. The energy distribution of the trap states with respect to conduction bands in the (Ni/Au) Schottky contact on AlInGaN/GaN heterostructures the relaxation time constant calculations for the trap states in the (Ni/Au) Schottky contact on AlInGaN/GaN heterostructures.